KAJIAN DISTRIBUSI C ORGANIK DAN KADAR AIR TAHAN DI LAHAN KOPI ROBUSTA KABUPATEN JEMBER DENGAN KETINGGIAN BERBEDA PADA AKHIR MUSIM PENGHUJAN - Purnamasari, Ika; Sanjaya, Rifqi Ilman; Rachman, Fatya; Priyono, Bagus Setyo Eko; Wijayanto, Yagus Wijayanto (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2024)
Coffee (Coffea spp.) is one of the leading commodities, which contributed 42.98 percent to the export value of the annual crop agricultural sector in 2013-2020. The productivity of Robusta coffee plants in the Jember region has tended to decrease significantly over the last 5 years. Geographic Information Systems (GIS) can be used to determine the distribution of organic C and soil water content as a basis for proper land management. The results showed that the percentage of ideal distribution area for organic C content was 94.94%, and the soil water content was at a value of 6.92-18.68%, where the status of moderate soil water content dominated by 59% of the total land. The results of simple linear regression analysis showed that the organic C variable (X1) had an effect of 29% and soil water content (X2) 10% productivity values. In addition, multiple linear regression analysis showed a strong influence of 63% on the value of productivity. The age factor also has an effect of 57% on the value of productivity.